Remedies containing agarwood in selected traditional malay medical manuscripts - Ummu Athiyah Mohammad Tormizi,; Nurhusna Samsudin,; Yumi Zuhanis Has-Yun Hashim,; Anis Najiha Ahmad,; Asmak Mutiah Mohd Nasir,; Nur Umisha Zainudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Agarwood (Aquilaria spp.) is an Asian native plant with various pharmaceutical potentials proven by recent scientific studies. It has been used for decades in ancient India, China, and the Malay Archipelago traditions. Ayurvedic and traditional Chinese medicine have been widely accepted and integrated into the current medical system. Regrettably, the traditional medicine of the Malay people has not reached this desired level despite the availability of knowledge as recorded in the Traditional Malay Medical (TMM) manuscripts. Agarwood is one of the materials observed in the traditional remedy formulations in TMM. Therefore, this work aims to explore the remedies in the TMM manuscripts with a focus on agarwood. Seven TMM manuscripts: MSS 2999, MSS 2515, MS 1998.400, Khazanah Perubatan Melayu Tumbuhan Ubatan, Kitab Tib Ilmu Perubatan Melayu, Khazinat al-Insan and Kitab al-Rahmah Fi al-Tibb wa alHikmah in the collection of the Malaysia National Library were reviewed systematically. The study finds around 100 agarwood-related formulations to treat around 20 diseases, including inner and physical illnesses, a specific approach to explicate the remedy that includes a discussion on selected Quranic verse and taboos, different sources of materials; plants, animals, and minerals, definitions on selected processing and dosing terms, three main methods to extract the materials; direct extraction, through heating or cooling, and maceration, and two ways to take the remedy; orally or externally. Findings from this study can be used as a reference for the practical application of the Malay traditional medication into current scientific development, verifying the relevancy of the discovery of new evident-based alternative medicine while safeguarding TMM as a national heritage.